An Uncommon Association: Eltrombopag and Autoimmune Hepatitis - Fady Salama; Hassnain Syed; Nimish Thakral (Case Reports in Hepatology)
Autoimmune hepatitis (AIH) is an immunological disorder of the liver characterized by hepatic necroinflammation due to the break in self-tolerance to autoantigens. Many medications have been linked to drug induced AIH. A review of the literature reveals no documented association between Eltrombopag and AIH. Eltrombopag is a thrombopoietin receptor agonist used to help manage thrombocytopenia in immune mediated thrombocytopenia and chronic liver disease. Here, we present a case of a 59-year-old female with refractory thrombocytopenia who was started on Eltrombopag, and later developed AIH.